What the marine geology of Table Bay, South Africa can inform about the western Saldania Belt, geological evolution and sedimentary dynamics of the region. (February 2020) - MacHutchon, M.R.; de Beer, C.H.; van Zyl, F.W.; Cawthra, H.C.
Abstract: Around the city of Cape Town, South Africa, the basal Neoproterozoic rocks are poorly exposed. There is however, historical evidence for good exposure of these rocks on the seafloor of Table Bay, although not mapped at sufficient resolution nor areal extent for significant conclusions. The Council for Geoscience therefore decided to commence their offshore mapping programme with this bay, mapping it at 1 m resolution using multibeam and sidescan sonar. The hope was that these data would help to unify the detailed sub-aerial investigations with offshore geological data. The seafloor outcrops are composed almost exclusively of rocks from the western branch of the Neoproterozoic Saldania Orogenic Belt and represent the largest exposure of the Tygerberg Formation regionally (~103 km 2 under water compared to ~2 km 2 exposed along the coastline). We demonstrate that the seafloor of Table Bay is an ideal locale to gain insight into the kinematics that have affected the rock mass on a regional scale. The outcrops display evidence of a shallow northwest-plunging anticline – syncline pair with associated smaller scale folds. The dip and strike of bedding planes delineate fold axial surface traces and fold type. The presence of lineaments and offset bedding suggest the presence of faults and/or fractures. The relative orientation of which is used to infer fault kinematics. Bedding truncation against a large northwest trending, linear, bathymetric low that is coincident with a weakly magnetic linear anomaly has led us to infer the presence of a regional Table Bay Fault zone. Lineaments interpreted as R1, R2 and P Riedel shears associated with this fault suggest sinistral strike-slip kinematics, similar to those recognised for other major fault zones on land with almost identical strike. The UNESCO world heritage site of Robben Island is located in the core of a syncline, its basal rocks composed of units marginally more arenaceous in character. The magnetic data acquired demonstrate the semi-continuous, anastomosing network of dolerite dykes within the Cretaceous False Bay Suite. Neogene features are absent in Table Bay, but as a result of Pleistocene sea level fluctuations, a complex palaeo-drainage network has incised into the seafloor during glacio-eustatically driven sea-level stillstands throughout the Quaternary Period. Highlights: Table Bay charted using highest possible resolution marine geophysical methods. Full seafloor coverage of both multibeam bathymetry and sidescan sonar. Structural kinematics of Neoproterozoic western Saldania Belt revealed. Complexity within Cretaceous False Bay Suite of dolerite dykes delineated using magnetics. Demonstration of how offshore outcrops can complement sparse onshore data.